Short Communication: Identification of marine leech and assessment of its prevalence and intensity on cultured hybrid groupers (Epinephelus sp.) - MURWANTOKO MURWANTOKO; SRI LAKSONO CONDRO NEGORO; ALIM ISNANSETYO; ZAFRAN ZAFRAN (Society for Indonesian Biodiversity, 2018)
Murwantoko, Negoro SLC, Isnansetyo A, Zafran. 2018. Short Communication: Identification of marine leech and determination of its prevalence and intensity on cultured hybrid groupers (Epinephelus sp.). Biodiversitas 19: 1798-1804. Grouper is an important fish species due to its high price both in domestic and international markets. Several hybrid groupers have been produced and can be accepted in market. A major production constraint in grouper culture is mortality due to diseases. Leech is an ectoparasite for groupers which may cause significant loss. The aims of this study were to identify and to assess the prevalence and intensity of leech on hybrid grouper cultured in sea cages at Buleleng waters. Morphological identification was conducted using fresh and stained specimens while molecular identification was conducted using nucleotides sequence of mitochondrial cytochrome oxidase subunit I (COI). The presence of leech was observed by unaided observation of 14 populations of hybrid grouper. Morphological identification showed that the leech belonged to Zeylanicobdella arugamensis. This result was also supported by analysis of COI sequence that showed 100% homology with Z. arugamensis (accession number KY 441721.1) and 90% homology with Aestabdella abditovesiculata (accession number DQ414300.1). Hybrid groupers at sea cages were infected by leeches with prevalence and intensity, respectively, of 100% and 21.2 leeches fish-1. The prevalence and intensity were varied depending on the farm and population. Cantik grouper was more susceptible to leech infection than cantang grouper. The bigger fish tended to have higher leech prevalence and intensity.